Compositional and surface characterization of HULIS by UV-Vis, FTIR, NMR and XPS: Wintertime study in Northern India. (September 2017) - Kumar, Varun; Goel, Anubha; Rajput, Prashant
Abstract: This study (first attempt) characterizes HULIS (Humic Like Substances) in wintertime aerosols (n = 12 during day and nighttime each) from Indo-Gangetic Plain (IGP, at Kanpur) by using various state-of-the art techniques such as UV-VIS, FTIR, 1 H NMR and XPS. Based on UV-Vis analysis the absorption coefficient at 365 nm (babs-365 ) of HULIS was found to average at 13.6 and 28.8 Mm −1 during day and nighttime, respectively. Relatively high babs-365 of HULIS during the nighttime is attributed to influence of fog-processing. However, the power fit of UV-Vis spectrum provided near similar AAE (absorption Angstrom exponent) value of HULIS centering at 4.9 ± 1.4 and 5.1 ± 1.3 during daytime and nighttime, respectively. FTIR spectra and its double derivative revealed the presence of various functional groups viz. alcohols, ketones aldehydes, carboxylic acids as well as unsaturated and saturated carbon bonds. 1 H NMR spectroscopy was applied to quantify relative percentage of various types of hydrogen atoms contained in HULIS, whereas XPS technique provided information on surface composition and oxidation states of various elements present. A significantly high abundance of H‒C‒O group has been observed in HULIS (based on 1 H NMR); 41.4± 2.7% and 30.9± 2.4% in day and nighttime, respectively. However, aromatic protons (Ar-H) were higher in nighttime samples (19.3± 1.8%) as compared to that in daytime samples (7.5 ± 1.9). XPS studies revealed presence of various species on the surface of HULIS samples. Carbon existed in 7 different chemical states while total nitrogen and sulfur exhibited 3 and 2 different oxidation states (respectively) on the surface of HULIS. This study reports structural information and absorption properties of HULIS which has implications to their role as cloud condensation nuclei and atmospheric direct radiative forcing. Graphical abstract: Highlights: Characterization of HULIS in terms of various functional groups and types of Hydrogens present along the carbon chain by FTIR nd H-NMR spectroscopy. Study of the surface composition and oxidation states of various elements present (XPS) on the HULIS molecules.